Investigating AI imitative capabilities: a comparative genre analysis of Reddit and ChatGPT-4 spouse appreciation posts - Arcenal, Erika Kristine Estanislao; Capistrano, Licca Pauleen Valdez; De Guzman, Marielle Jessie Dela Peña; Forrosuelo, Micaela Isabel Molina; Miranda, Janeson Mirabuna (Penerbit Universiti Kebangsaan Malaysia, 2025)
ChatGPT-4 has been a helping tool for its users in various fields and contexts. Among these, a recurring topic of inquiry is AI’s ability to mimic human language, particularly appreciative sentiments. In this study, we explore the current capabilities of ChatGPT-4 at mimicking human appreciatory language by comparing its prompt-based generated texts to the appreciative posts of married individuals on Reddit, specifically subreddit r/Marriage. Using Swales' moves analysis as the working framework, we determined and then labelled moves found in the Reddit posts as we examined them as a genre and compared them with AI-generated posts. Findings revealed that ChatGPT-4 imitated 11 out of the 13 moves present in the Reddit posts. Furthermore, five categories of obligatory moves were established to better distinguish between the texts. ChatGPT-4 was observed to have more clearly obligatory moves and was more consistent in following a certain sequence than texts written by a human being. Additionally, ChatGPT- 4 generated texts had a higher average word count and gave an impersonal impression due to its lack of the following moves: Description of Spouse, Description of Original Poster, and Relationship Background. With these findings, we recommend further linguistic studies on Reddit posts and other non-academic social media forms as a genre and the continuous use of genre analysis to circumscribe, more precisely, the AI imitative capabilities of human natural language and its implications to future applications.